BODY IMAGE PERCEPTION OF CHILDREN WHO PRACTICE DANCE-SCHOOL EDUCATION IN PUBLIC. (Fiep Bulletin - online, 2012)
Body image is directly related to the self, which is defined by the set of values and beliefs, conscious or accessible toconsciousness, as well as attitudes and opinions that the individual has of himself in relation to the other and the world (Miranda ,2011). Prusinsky & Cash (2002), argue that the perceptual dimension of body image has often been used, mainly in health, in anattempt to assess how the individual perceives the form and / or size of your body. The study found the screen like a child whopractices dance education perceive their body image. It was held at the Municipal School of Elementary Education Our Lady ofPerpetual Help - NSPS in the city of Fortaleza, Brazil, with a sample of seventeen children between eight and twelve years of agewho do dance at school. The research is exploratory descriptive qualitative approach. As data collection instrument for theassessment of body image perception was applied Set of silhouettes proposed by Stunkard et al (1983). It was found that obesechildren do not have choices associated with the representation of low weight, and that the self-assessment of body size andshape, was leading with choices lean body, consistent with reality. The data indicate that the silhouettes that represent the currentsize and shape, selected for obese children, appeared distorted and associated with the standard thin body, widely publicized bythe media, pointing at the difficulties relating to the perception of body image and health.
Keywords: Dance-Education. Body Image. School.